Exploring the therapeutic efficacy of ethanol extracts from Melia azedarach Linn. fruit-seeds against oxidative stress induced by melon flies on bitter melon. - Nhung, T. T. P.; Quoc, L. P. T. (International Journal of Agricultural Technology, 2025)
The application of ethanol extract of fruit-seeds Melia azedarach (FSMA) resulted in a significant, concentration-dependent reduction in malondialdehyde (MDA) and hydrogen peroxide (H2O2) levels (p < 0.05), indicating a marked attenuation of oxidative stress. Enzymatic assays demonstrated that FSMA treatments, particularly at 125 and 652 ppm, significantly enhanced the activities of key antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD). A strong inverse correlation was observed between the levels of oxidative stress biomarkers and the activities of these antioxidative enzymes, suggesting a mechanistic role of FSMA in modulating redox homeostasis. The findings underscore the efficacy of FSMA in mitigating oxidative damage through the activation of endogenous antioxidant defense systems. These results support the potential use of FSMA as a sustainable and natural alternative to synthetic pesticides, contributing to the development of eco-friendly strategies for oxidative stress management in agricultural systems.